Rhizodeposition mediates the effect of nitrogen and phosphorous availability on microbial carbon use efficiency and turnover rate. (March 2020) - Bicharanloo, Bahareh; Bagheri Shirvan, Milad; Keitel, Claudia; Dijkstra, Feike A.
Abstract: Soil microorganisms affect both the formation and decomposition of soil organic carbon (SOC). We investigated how nitrogen (N, 25 vs. 100 kg N ha −1 ) and phosphorus (P, 10 vs. 40 kg P ha −1 ) fertilisation influenced microbial C use efficiency (CUE) and turnover rate in soil planted with two wheat genotypes, and to what degree these parameters were associated with microbial use of root- and soil-derived C (MBCroot and MBCsoil, respectively). We used a H2 18 O labeling method to quantify CUE and turnover rate, and a continuous 13 CO2 plant labelling method to characterise MBCroot and MBCsoil . We found that N fertilisation decreased CUE and slowed down turnover rate, but only at the highest P-level. In contrast, N fertilisation increased MBCsoil at high P, while it increased MBCroot at low P. MBCsoil was negatively and MBCroot was positively related to CUE and microbial turnover rate. Our results suggest that microbes that used more labile root-derived C built up their biomass more efficiently than microbes using more recalcitrant soil-derived C. A more efficient use of root-derived C could enhance the microbially mediated formation of root-derived SOC, but the higher turnover rate and associated C recycling may counter this effect. In contrast, the lower CUE and turnover rate of microbes using more soil-derived SOC suggests that these microbes spent more C on maintenance due to C limitation, which particularly occurred under high N and high P fertilisation. We conclude that fertiliser-induced changes in root-derived C availability play an important role in CUE, MBC pools and microbial turnover rate, ultimately affecting SOC sequestration. Graphical abstract: Image 1 Highlights: Fertiliser induced changes in root-derived C incorporation into MBC. N fertilisation increased MBCroot under low P as a result of higher rhizodeposition. N fertilisation increased MBCsoil under high P as rhizodeposition reduced. Rhizodeposition mediated the N and P fertilization effect on CUE and turnover. Microbes used labile root-derived C more efficiently than recalcitrant SOC.